"Wait! I don't get it! Can we translate?": Explicit collaborative translation to support emergent bilinguals' reading comprehension in the intermediate grades. Issue 2 (2nd April 2020) - Cano, Jessica; Ruiz, Nadeen Teresa
ABSTRACT: Throughout our targeted approach of explicit collaborative translation during small-group reading instruction in a bilingual education classroom, fourth grade emergent bilinguals employed the strategy to comprehend narrative text in a range of ways, similar to middle school students in reading instruction research. As students acknowledged the usefulness of their translation skills in constructing meaning with text, they also demonstrated increased initiative to engage in reading across classroom literacy events. Findings from this exploratory inquiry, including initial evidence of students' developing bilingual identities of competence, suggest further research is warranted on explicit collaborative translation as part of a growing corpus of evidence-based translingual practices in bilingual classrooms.